2019
DOI: 10.1590/2177-6709.24.6.048-055.oar
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fluoride associated with nano-hydroxyapatite in reducing enamel demineralization adjacent to orthodontic brackets: in situ study

Abstract: Objective: To assess in situ the effect of fluoride associated with nano-hydroxyapatite for the prevention of demineralization of the enamel adjacent to orthodontic brackets. Material and Methods: Eight volunteers wore palatal devices prepared with 6 bovine enamel blocks (5x5x2 mm) with bonded brackets. The volunteers used the devices in two different moments of 14 days each. During the first 14 days, a product containing fluoride + nano-hydroxyapatite was applied twice (experimental group, GNH, n = 48), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
7
1
1
Order By: Relevance
“…This is supported by a study that investigated the synergistic effects of fluoride and nano-HA on preventing enamel demineralisation around orthodontic brackets [29]. Results revealed significantly less demineralisation depth in the combined nano-HA and fluoride group [29]. Additionally, the combination of nano-HA with fluoride has shown better enamel resistance to erosion in bovine teeth [52].…”
Section: Hydroxyapatite In Oral Care Productsmentioning
confidence: 80%
See 3 more Smart Citations
“…This is supported by a study that investigated the synergistic effects of fluoride and nano-HA on preventing enamel demineralisation around orthodontic brackets [29]. Results revealed significantly less demineralisation depth in the combined nano-HA and fluoride group [29]. Additionally, the combination of nano-HA with fluoride has shown better enamel resistance to erosion in bovine teeth [52].…”
Section: Hydroxyapatite In Oral Care Productsmentioning
confidence: 80%
“…However, more studies are needed to determine the optimal nano-HA and NaF mouth rinse conditions for human use [51]. This is supported by a study that investigated the synergistic effects of fluoride and nano-HA on preventing enamel demineralisation around orthodontic brackets [29]. Results revealed significantly less demineralisation depth in the combined nano-HA and fluoride group [29].…”
Section: Hydroxyapatite In Oral Care Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface roughness of the two halves of a tooth is probably not the same. Kislyakov, 2020 in their study by profiling investigate the effect of regular drinks on the microhardness of enamel and the result found that the enamel microhardness decreased after consuming beverages [4,11,12].…”
Section: Advances In Dentistry and Oral Healthmentioning
confidence: 99%